My exciting journey in biochemistry: A year at Wythenshawe Hospital - Heba Toumeh (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Heba Toumeh, a Biomedical Science placement student, spent a year working towards her IBMS Certificate of Competence by building her portfolio; she has now successfully passed her verification. She talks about her time at Wythenshawe Hospital, a part of Manchester University NHS Foundation Trust. She provides an insight into what life is like as a placement student, looking at the day to day running of a Biochemistry lab as well as the challenges faced by Biomedical Scientists.